Estimating Tertiary EFL Students’ Enjoyment During Online Language Classes - Rosmen, Rosmen (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study purposively conducted to investigate the EFL students’ feeling during online learning in the pandemic situation and confirm their assumption on their teachers’ approach providing the online classes. A survey to the seventy-seven students of STKIP Al Maksum Langkat was conducted. The psychometrically validated short form consists of nine positively-phrased items proposed by Resnik & Dewaele (2021) were distributed via Google Form which were classified in to three categories: ‘personal enjoyment’ (e.g., “In my online or ‘in-person’ English class, I feel proud of my accomplishments”), ‘social enjoyment’ (e.g., “We laugh a lot” in the online class) and ‘teacher appreciation’ (to what extent the teacher is perceived as encouraging, friendly and supportive). The result asserted that students mostly strongly agree that there was no boredom in their online learning due to their understanding about school-closure because of the pandemic. Further, online learning environment affecting students’ low participation so that their collaboration in the online classes straitened their feeling. Nevertheless, the perspectives of the teachers on the situation as well as their understanding of the advantages of online appliances have an effect on the enjoyment of the students.